1987
DOI: 10.1139/f87-175
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod Control of Parr–Smolt Transformation in Atlantic Salmon (Salmo salar): Changes in Salinity Tolerance, Gill Na+,K+-ATPase Activity, and Plasma Thyroid Hormones

Abstract: Atlantic salmon (Salmo salar) were subjected to artificial photoperiods to determine the manner and extent of photoperiod control of the parr–smolt transformation. Exposure to continuous light (L24) at first feeding and maintained throughout the rearing period inhibited increases in salinity tolerance and gill Na+,K+-ATPase activity that occurred in spring in fish raised under simulated natural photoperiod (SNP). Fish reared under continuous light and returned to SNP in October (L24OCT) underwent normal increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(66 citation statements)
references
References 0 publications
6
58
2
Order By: Relevance
“…For most of these species, the reduction of day length reduces the growth (McCormick et al, 1987, Stefansson et al, 1989, which can be observed in both freshwater (Saunders et al, 1985;Stefansson et al, 1989;Solbakken et al, 1994) and saltwater salmon (Saunders and Harmon, 1988;Krakenes et al, 1991;Hansen et al, 1992). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most of these species, the reduction of day length reduces the growth (McCormick et al, 1987, Stefansson et al, 1989, which can be observed in both freshwater (Saunders et al, 1985;Stefansson et al, 1989;Solbakken et al, 1994) and saltwater salmon (Saunders and Harmon, 1988;Krakenes et al, 1991;Hansen et al, 1992). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on the influence of photoperiod on fish (McCormick et al, 1987;Krakenes et al, 1991;Bromage, 1995;Cerqueira and Brügger, 2001). Most of those studies were carried out with saltwater fishes or freshwater fishes from the northern hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the change of this enzyme activity is a good indicator of seawater adaptability and potential for growth in seawater. 4,[7][8][9] In the present seawater challenge test, gill Na+-K+AT In the seawater rearing test, no parr-smolt transforma tion was observed, indicating seawater adaptability of this fish is not always coincided with smoltification as de scribed previously,10-12) The gill Na+-K+ATPase activity at 103 days after seawater transfer increased up to 9 times, when compared with the initial value. Coinciding with the change of this enzyme activity, serum Na concentration decreased almost to the initial value.…”
Section: Discussionmentioning
confidence: 52%
“…External stimuli like light trigger the smoltification process, and several hormones involved in the smoltification process (GH, PRL) have been identified (McCormick et al 1987). On the basis of this study calcitriol can be added to the list of hormones involved or taking part in the smollification process.…”
Section: Smoltification and Vitamin D: Pre-adaptation To Swmentioning
confidence: 99%